Promoting Higher Levels of Learner Autonomy in Blended Learning Academic English Programmes - Elsayed Hamed Ibrahim, Mahmoud; Ata Alkhaldi, Ali; Gabriel, Raafat (Forum for Linguistic Studies, 2025)
The paper systematically reviews the impact of blended learning (BL) on learner autonomy (LA), with particular emphasis on learners from diverse cultural and educational backgrounds. The study focuses on academic English and courses designed for international students enrolled in pre-university and transitional programmes, which serve as prerequisites for undergraduate or postgraduate studies in the United Kingdom. International students bring substantial value in terms of soft power, global influence, and financial benefit. Their presence is also reported to enrich the educational experience by introducing diverse perspectives and encouraging a more stimulating, inclusive, and dynamic learning environment. This study compares, analyses and synthesises the findings of 17 scholarly research papers published between 2015 and 2025 to examine autonomous learning. It outlines the characteristics of autonomous learners and aims to develop a profile of these learners within BL contexts. This profile helps educators tailor instructional approaches to better support learners from diverse backgrounds. The indispensable role of instructional technology—and technology more broadly—within BL environments influences both the level and sustainability of autonomous learning. Accordingly, the article explores the development of LA through both embedding /integrating technology in BL and the availability of learning resources. Finally, the study examines the role of cognitive, metacognitive, affective, and social language learning strategies in cultivating LA among this category of international students, emphasising their long-term academic success.